Characterization of the family experience of children and adolescents with Diabetes mellitus type 1: a narrative review (Research, Society and Development, 2022)
Diabetes Mellitus (DM) is a chronic health condition characterized by hyperglycemia resulting from the impossibility of production or deficiency in the secretion or action of insulin. Type 1 DM is the most frequent in children and adolescents. This study aims to investigate characteristics of family life after the diagnosis of type 1 diabetes mellitus in children and adolescents and the possible difficulties encountered after this period. This is a narrative review, with a search for papers in the Latin American and Caribbean Literature in Health Sciences (Lilacs), Pubmed/Medline, Scientific Electronic Library Online (Scielo) and Cochrane databases with studies published in the last 20 years. It is evidenced by the studies that the discovery of the disease impacts the routine and changes in the family lifestyle, showing as the main difficulties the application of insulin and proposed dietary adaptations, added to feelings such as guilt, fear, anxiety and frustration. In these circumstances, the support of guardians is essential for the acceptance and control of the disease by the child or adolescent. The changes evidenced can cause psychological and emotional changes, as well as in the well-being and in the proper course of the disease, thus suggesting the need for support and guidance focused on improving the quality of life of children and adolescents and their families.